2000
DOI: 10.1074/jbc.275.15.10943
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin Is a WT1 Target Gene

Abstract: The WT1 tumor suppressor gene encodes a transcription factor that can activate and repress gene expression. Transcriptional targets relevant for the growth suppression functions of WT1 are poorly understood. We found that mesenchymal NIH 3T3 fibroblasts stably expressing WT1 exhibit growth suppression and features of epithelial differentiation including up-regulation of E-cadherin mRNA. Acute expression of WT1 in NIH 3T3 fibroblasts after retroviral infection induced murine Ecadherin expression. In transient t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 65 publications
3
83
2
Order By: Relevance
“…On the other hand, WT1 directly transactivates E-cadherin, suggesting that loss of WT1 may also repress the Ecadherin gene. 37 In order to assess whether similar relationships exist in mouse hepatocarcinogenesis, we have determined the expression levels of Snail, Slug, HIF-1a and WT1 by Western blot analysis in the same collection of mouse HCCs. The results of our analysis are shown in Figure 2.…”
Section: Western Blot Analysis Of Snail Slug Hif-1a Vegf and Wt1mentioning
confidence: 99%
“…On the other hand, WT1 directly transactivates E-cadherin, suggesting that loss of WT1 may also repress the Ecadherin gene. 37 In order to assess whether similar relationships exist in mouse hepatocarcinogenesis, we have determined the expression levels of Snail, Slug, HIF-1a and WT1 by Western blot analysis in the same collection of mouse HCCs. The results of our analysis are shown in Figure 2.…”
Section: Western Blot Analysis Of Snail Slug Hif-1a Vegf and Wt1mentioning
confidence: 99%
“…These include the EGFR, IGF1R, BCL2, amphiregulin, E-cadherin and ornithine decarboxylase. [1][2][3][4][5][6] WT1 can regulate transcription through both activator and suppressor functions and this is affected by the cellular environment in which it is expressed.…”
mentioning
confidence: 99%
“…The precise nature of the role of WT1 in this process is however not known, although there is evidence that transactivation of the WT1 target genes, amphiregulin and E-cadherin, may be involved. 5,6 Oncogenic WT1 lesions have been identified in tumors arising in tissues of mesodermal origin including the kidney (Wilms' tumor) 8 gut-lining (Desmoplastic small round cell tumor) 9 and lungs (mesothelioma). 10 In addition, germline heterozygous WT1 zinc-finger mutations occur in Denys Drash syndrome in which patients are predisposed to the development of both Wilms' tumor and gonadoblastoma.…”
mentioning
confidence: 99%
“…While initial experiments associated growth suppression and characteristics of epithelial differentiation, including upregulation of E-cadherin, with stable expression of WT1 in NIH 3T3 cells (62), more recent studies in cardiac epithelial cells showed that WT1 transcriptionally repressed E-cadherin expression both directly and indirectly by the upregulation of Snail (28). Furthermore, it has been demonstrated that WT1 expression promotes metastasis and invasion in nonsmall-cell lung carcinoma patients through the suppression of E-cadherin (90).…”
Section: Wt1 Suppression Of E-cadherin Promotes Cell Motilitymentioning
confidence: 99%
“…Initial studies in NIH-3T3 cells, in which it was demonstrated that E-cadherin is a WT1 target gene (62), and studies in cardiac epithelial cells have established the role of WT1 in E-cadherin regulation (28). E-cadherin is a transmembrane protein that mediates epithelial cell-cell interactions in the adherent junctions of the plasma membrane (63) through homophilic proteinprotein interactions (64).…”
Section: Wt1 Suppression Of E-cadherin Promotes Cell Motilitymentioning
confidence: 99%